Elaboración de un plan estratégico para la empresa de construcción Procivin S.A.S. (2020)
The present work of degree elaborates a strategic plan for a company of the construction sector, dedicated to the study, design, planning, coordination, and construction of civil engineering works and architecture. First, a diagnosis is made using tools such as PESTAL analysis (Colombia and Bogotá). Likewise, a sector analysis was carried out and later a self-diagnosis was carried out by the Bogotá Chamber of Commerce. Then, a DOFA (Weaknesses, Opportunities, Strengths and Threats) analysis was carried out, where the position of the company in the sector was identified and strategies were proposed for the context in which the company carries out its activities.